Coating agent, laminate fiber cloth and method for producing the same
A coating agent with a specific resin and polyvalent metal salt combination addresses the issue of resin penetration in non-fluorine treated fiber fabrics, enhancing windproof properties and durability.
Patent Information
- Application Number
- JP2023107322
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Existing methods for imparting windproof properties to fiber fabrics using non-fluorine water repellents and resins result in insufficient performance, particularly after washing, due to resin penetration and poor film adhesion.
A coating agent comprising a resin (A) with a specific aromatic ring ratio and a polyvalent metal salt (B) is applied to one side of a fiber fabric treated with a non-fluorine water repellent, forming a laminated structure that enhances windproof properties by preventing resin penetration and ensuring durable adhesion.
The coating agent provides excellent windproof properties, especially after washing, with improved film adhesion and texture, while maintaining flexibility and breathability.
Smart Images

Figure 2025006497000001 
Figure 2025006497000002 
Figure 2025006497000003
Abstract
Description
[Technical field]
[0001] The present application discloses a coating agent, a laminated fiber fabric, and a method for producing the same. [Background technology]
[0002] Patent Document 1 discloses a technique for imparting wind resistance to a fiber fabric by applying a resin (coating agent) to one side of the fiber fabric to form a resin film (coating agent film). When resin is applied to the fiber fabric, the resin may penetrate (strike through) from the applied side to the opposite side of the fiber fabric, making it impossible to form a desired resin film on one side of the fiber fabric.
[0003] Patent Document 2 discloses a technique for imparting wind resistance and the like to a fiber fabric by applying a water repellent to the fiber fabric and then applying a resin (coating agent) to one side of the fiber fabric to form a resin film (coating agent film). By applying a resin to a fiber fabric to which a water repellent has been applied as disclosed in Patent Document 2, it is possible to prevent the resin from penetrating (stripping through) to the side of the fiber fabric opposite to the coated side. Examples of water repellents include fluorine-based water repellents and non-fluorine-based water repellents, but it can be said that it is preferable to use a non-fluorine-based water repellent that has little impact on the environment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-127253 A [Patent Document 2] JP 2018-009268 A Summary of the Invention [Problem to be solved by the invention]
[0005] According to the new findings of the present inventor, the performance of the resin film (coating agent film) formed on the surface of the fiber fabric is different when a resin (coating agent) is applied to a fiber fabric to which a non-fluorine-based water repellent agent has been applied and when a resin (coating agent) is applied to a fiber fabric to which a fluorine-based water repellent agent has been applied. For example, when a resin (coating agent) is applied to a fiber fabric to which a non-fluorine-based water repellent agent has been applied, the performance of the resin film (coating agent film) may not be sufficient, and good wind resistance may not be obtained. In particular, there is room for improvement in wind resistance after washing.
[0006] The present application discloses a coating agent capable of imparting excellent windproof properties (particularly windproof properties after washing) to a fiber fabric to which a water repellent has been applied, a laminated fiber fabric using the coating agent, and a method for producing the laminated fiber fabric. [Means for solving the problem]
[0007] The present application discloses the following aspects as means for solving the above problems. <Aspect 1> A coating agent comprising a resin (A) and a polyvalent metal salt (B), The resin (A) is one or both of a copolymer resin (A1) and a mixed resin (A2), The copolymer resin (A1) is A unit (u1) derived from a radical polymerizable monomer (a1) represented by the following formula (1), A unit (u2) derived from a radical polymerizable monomer (a2) represented by the following formula (2): having The mixed resin (A2) is A resin (A2-1) having the unit (u1), A resin (A2-2) having the unit (u2), It is a combination of The aromatic ring ratio of the resin (A) is 0.5% or more and 30% or less. Coating agent. [ka] In formula (1), R 101 represents an optionally substituted C6 to C20 aryl group, R 102 represents hydrogen, a C1-24 saturated hydrocarbon group which may have a substituent, or a C6-20 aryl group which may have a substituent, X 101 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-; X 102 is a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-. [ka] In formula (2), R 201 is a carboxy group, R 202 represents hydrogen or a C1 to C24 saturated hydrocarbon group which may have a substituent, R 203 represents hydrogen or a C1 to C24 saturated hydrocarbon group which may have a substituent, R 204 represents hydrogen, a carboxy group, or a C1 to C24 saturated hydrocarbon group which may have a substituent, X 201 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-; X 202 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-; X 203 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-; X 204 is a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-. <Aspect 2> the ratio of the mass of the polyvalent metal salt (B) to the mass of the unit (u2) constituting the resin (A) is 1.0% or more and 10.0% or less; The coating of embodiment 1. <Aspect 3> The glass transition temperature Tg of the resin (A) is -40°C or higher and 0°C or lower. 3. The coating agent of embodiment 1 or 2. <Aspect 4> The acid value of the resin (A) is 1 or more and 20 or less. The coating agent according to any one of embodiments 1 to 3. <Aspect 5> A laminated fiber fabric having a fiber fabric, a water-repellent coating, and a coating agent coating, the water-repellent coating contains a non-fluorinated water-repellent agent, The water-repellent coating is formed on at least a portion of the fiber fabric, The coating agent film is formed on one side of the fiber fabric, the coating agent film is formed on at least a part of the surface of the water-repellent film, The coating agent film is made of the coating agent according to any one of aspects 1 to 4. Laminated fiber fabric. <Aspect 6> 1cm 3 / cm 2 ·S or less air permeability, 2cm 3 / cm 2 ·S or less durable air permeability, The laminated fiber fabric of embodiment 5. <Aspect 7> A method for producing a laminated fiber fabric, comprising: Treating a fiber fabric with a first treatment liquid to obtain a water-repellent fabric; and Treating one surface of the water-repellent fabric with a second treatment liquid; the first treatment liquid contains a non-fluorinated water repellent agent, The second treatment liquid contains the coating agent according to any one of aspects 1 to 4. Manufacturing method. <Aspect 8> The second treatment liquid is applied to one side of the water-repellent fabric by a coating method. The method of manufacture of embodiment 7. <Aspect 9> The viscosity of the second treatment liquid is 5,000 mPa·s or more and 50,000 mPa·s or less. The method for producing aspect 7 or 8. Effect of the Invention
[0008] The coating agent of the present disclosure can impart excellent windproof properties (especially windproof properties after washing) to a fiber fabric to which a water repellent agent has been applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, a coating agent, a laminated fiber fabric, and a method for producing the same according to one embodiment will be described, but the coating agent, the laminated fiber fabric, and the method for producing the same according to the present disclosure are not limited to this embodiment.
[0010] 1. Coating agent The coating agent according to one embodiment includes a resin (A) and a polyvalent metal salt (B). The resin (A) is one or both of a copolymer resin (A1) and a mixed resin (A2). The copolymer resin (A1) has a unit (u1) derived from a radical polymerizable monomer (a1) represented by the following formula (1) and a unit (u2) derived from a radical polymerizable monomer (a2) represented by the following formula (2). The mixed resin (A2) is a combination of a resin (A2-1) having the unit (u1) and a resin (A2-2) having the unit (u2). The aromatic ring ratio of the resin (A) is 0.5% or more and 30% or less.
[0011] [ka] In formula (1), R 101 represents an optionally substituted C6 to C20 aryl group, R 102represents hydrogen, a C1-24 saturated hydrocarbon group which may have a substituent, or a C6-20 aryl group which may have a substituent, X 101 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-; X 102 is a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-.
[0012] [ka] In formula (2), R 201 is a carboxy group, R 202 represents hydrogen or a C1 to C24 saturated hydrocarbon group which may have a substituent, R 203 represents hydrogen or a C1 to C24 saturated hydrocarbon group which may have a substituent, R 204 represents hydrogen, a carboxy group, or a C1 to C24 saturated hydrocarbon group which may have a substituent, X 201 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-; X 202 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-; X 203 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-; X 204 is a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-.
[0013] 1.1 Resin (A) The resin (A) is one or both of the copolymer resin (A1) and the mixed resin (A2). That is, the resin (A) may be composed of only the copolymer resin (A1), may be composed of only the mixed resin (A2), or may be a combination of the copolymer resin (A1) and the mixed resin (A2). The resin (A) may be composed of one type of resin or may be composed of multiple types of resin. In particular, when the resin (A) is composed of two or more types of resin, more excellent performance is likely to be exhibited. On the other hand, when the resin (A) is composed of three or less types of resin, the labor of adjustment can be saved. Preferably, the resin (A) is composed of two types of resin.
[0014] 1.1.1 Copolymer resin (A1) The copolymer resin (A1) has a unit (u1) derived from a radical polymerizable monomer (a1) represented by the above formula (1) and a unit (u2) derived from a radical polymerizable monomer (a2) represented by the above formula (2). The copolymer resin (A1) may be composed of one type of copolymer resin or may be composed of multiple types of copolymer resins.
[0015] <Radically polymerizable monomer (a1) represented by formula (1)> As represented by formula (1), the radically polymerizable monomer (a1) has an aromatic ring in addition to a radically polymerizable group.
[0016] In formula (1), R 101is a C6-20 aryl group which may have a substituent. Examples of the C6-20 aryl group which may have a substituent include a phenyl group, a phenylphenyl group, a benzylphenyl group, a cumylphenyl group, an alkylphenyl group (such as a tolyl group, a xylyl group, a butylphenyl group, an octylphenyl group, a nonylphenyl group, or a dodecylphenyl group), a naphthyl group, a phenylnaphthyl group, a benzylnaphthyl group, a cumylnaphthyl group, an alkylnaphthyl group (such as a butylnaphthyl group, an octylnaphthyl group, or a nonylnaphthyl group), or a group in which some or all of the hydrogen atoms bonded to these groups are substituted with a halogen, an amino group, a cyano group, a methoxy group, an ethoxy group, an acetamide group, or an acetyl group. In formula (1), R 101 When is a phenyl group or a benzyl group, particularly when it is a phenyl group, even more excellent performance is likely to be ensured.
[0017] In formula (1), R 102 is hydrogen, a C1-24 saturated hydrocarbon group which may have a substituent, or a C6-20 aryl group which may have a substituent. The C1-24 saturated hydrocarbon group may be linear or branched, and may have an alicyclic structure. Examples of the substituent include halogen, an amino group, a cyano group, a methoxy group, an ethoxy group, an acetamide group, and an acetyl group. The C6-20 aryl group which may have a substituent is as described above. In formula (1), R 102 When is hydrogen, even better performance is likely to be ensured.
[0018] In formula (1), X 101 is a single bond, a C1-10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-. The C1-10 divalent hydrocarbon group may be saturated or unsaturated, may be linear or branched, may be an aliphatic hydrocarbon group or an aromatic hydrocarbon group, or may have an alicyclic structure. In formula (1), X 101 When is a single bond or -COO-, particularly when it is a single bond, even more excellent performance is likely to be ensured.
[0019] In formula (1), X102 is a single bond, a C1-10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-. The C1-10 divalent hydrocarbon group is as described above. In formula (1), X 102 When is a single bond or -COO-, particularly when it is a single bond, even more excellent performance is likely to be ensured.
[0020] In formula (1), R 101 is a phenyl or benzyl group, in particular a phenyl group, R 102 is hydrogen and X 101 and X 102 However, when each is independently a single bond or -COO-, and particularly when both are single bonds, even more excellent performance is likely to be ensured. Examples of the radical polymerizable monomer (a1) that satisfies this requirement include one or both of styrene and benzyl acrylate. From the viewpoint of adhesion (less film peeling), it is preferable that the radical polymerizable monomer (a1) is styrene.
[0021] <Radically polymerizable monomer (a2) represented by formula (2)> As represented by formula (2), the radically polymerizable monomer (a2) has a carboxy group in addition to a radically polymerizable group.
[0022] In formula (2), R 201 is a carboxy group. The carboxy group can bond with a metal ion derived from the polyvalent metal salt (B) described below.
[0023] In formula (2), R 202 is hydrogen or a C1-24 saturated hydrocarbon group which may have a substituent. The C1-24 saturated hydrocarbon group may be linear or branched, and may have an alicyclic structure. Examples of the substituent include halogen, amino group, cyano group, methoxy group, ethoxy group, acetamide group, and acetyl group. In formula (2), R 202 When is hydrogen or a C1 to C24 saturated hydrocarbon group, even more excellent performance is likely to be ensured.
[0024] In formula (2), R 203 is hydrogen or a C1-24 saturated hydrocarbon group which may have a substituent. The C1-24 saturated hydrocarbon group is as described above. In formula (2), R 203 When is hydrogen, even better performance is likely to be ensured.
[0025] In formula (2), R 204 is hydrogen, a carboxy group, or a C1-24 saturated hydrocarbon group which may have a substituent. The C1-24 saturated hydrocarbon group is as described above. The carboxy group can bond to a metal cation derived from the polyvalent metal salt (B) described later. In formula (2), R 204 When is hydrogen, even better performance is likely to be ensured.
[0026] In formula (2), X 201 is a single bond, a C1-10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-. The C1-10 divalent hydrocarbon group may be saturated or unsaturated, may be linear or branched, may be an aliphatic hydrocarbon group or an aromatic hydrocarbon group, or may have an alicyclic structure. In formula (2), X 201 When is a single bond or -COO-, particularly when it is a single bond, even more excellent performance is likely to be ensured.
[0027] In formula (2), X 202 is a single bond, a C1-10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-. The C1-10 divalent hydrocarbon group is as described above. In formula (2), X 202 When is a single bond or -COO-, particularly when it is a single bond, even more excellent performance is likely to be ensured.
[0028] In formula (2), X 203 is a single bond, a C1-10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-. The C1-10 divalent hydrocarbon group is as described above. In formula (2), X 203When is a single bond or -COO-, particularly when it is a single bond, even more excellent performance is likely to be ensured.
[0029] In formula (2), X 204 is a single bond, a C1-10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-. The C1-10 divalent hydrocarbon group is as described above. In formula (2), X 204 When is a single bond or -COO-, particularly when it is a single bond, even more excellent performance is likely to be ensured.
[0030] In formula (2), R 101 is a carboxy group, and R 102 is hydrogen or a saturated hydrocarbon group having 1 to 24 carbon atoms; R 103 and R 104 is hydrogen and X 101 , X 102 , X 103 and X 104 are each independently a single bond or -COO-, particularly when all are single bonds, more excellent performance is likely to be ensured. Examples of the radical polymerizable monomer (a2) that satisfies this requirement include one or both of acrylic acid and methacrylic acid. From the viewpoint of stability of the emulsion dispersion of the resin (A), it is preferable that the radical polymerizable monomer (a2) is one or both of acrylic acid and methacrylic acid.
[0031] <Other monomers (a3)> The copolymer resin (A1) may be composed of units (u1) and (u2) derived from the above radical polymerizable monomers (a1) and (a2), or may contain units derived from other monomers in addition to the units (u1) and (u2). Examples of other monomers include the radical polymerizable monomer (a3) represented by the following formula (3).
[0032] [ka] In formula (3), R 301 , R302 , R 303 and R 304 each independently represents hydrogen or a C1 to C24 saturated hydrocarbon group which may have a substituent, X 301 , X 302 , X 303 and X 304 are each independently a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-.
[0033] In formula (3), the C1-24 saturated hydrocarbon group may be linear or branched, or may have an alicyclic structure. Examples of the substituent include halogen, amino, cyano, methoxy, ethoxy, acetamide, and acetyl groups. The C1-10 divalent hydrocarbon group may be saturated or unsaturated, linear or branched, an aliphatic hydrocarbon group or an aromatic hydrocarbon group, or may have an alicyclic structure.
[0034] In formula (3), R 301 is a C1-24 saturated hydrocarbon group which may have a substituent, R 302 , R 303 and R 304 are each independently hydrogen or a C1 to C24 saturated hydrocarbon group which may have a substituent, X 301 is -COO-, and X 302 , X 303 and X 304 are each independently a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-, better performance is likely to be ensured; In particular, R 301 is a C1-24 saturated hydrocarbon group which may have a substituent, R 302 , R 303 and R 304 are each independently a hydrogen atom or a methyl group; X 301is -COO-, and X 302 , X 303 and X 304 However, when the bond is a single bond, more excellent performance is likely to be ensured. As the radical polymerizable monomer (a3) that satisfies this requirement, at least one of butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, and 2-hydroxyethyl methacrylate can be mentioned.
[0035] <Copolymerization ratio> In the copolymer resin (A1), the ratio of the unit (u1) derived from the radical polymerizable monomer (a1) represented by formula (1) to the unit (u2) derived from the radical polymerizable monomer (a2) represented by formula (2) may be such that the aromatic ring ratio described below is satisfied in the entire resin (A). In addition, in the copolymer resin (A1), the ratio of the unit derived from other monomers (for example, the above-mentioned radical polymerizable monomer (a3)) is not particularly limited, and may be such that the aromatic ring ratio described below is satisfied. In one embodiment, the ratio of the radical polymerizable monomer (a1) to all monomers constituting the copolymer resin (A1) may be 0.5 mol% or more and 50 mol% or less, or 10 mol% or more and 30 mol% or less, the ratio of the radical polymerizable monomer (a2) to all monomers constituting the copolymer resin (A1) may be 1 mol% or more and 10 mol% or less, or 2 mol% or more and 5 mol% or less, and the total ratio of the radical polymerizable monomer (a1) and the radical polymerizable monomer (a2) to all monomers constituting the copolymer resin (A1) may be 1.5 mol% or more and 60 mol% or less, or 12 mol% or more and 35 mol% or less.
[0036] 1.1.2 Mixed resin (A2) The mixed resin (A2) is a combination of a resin (A2-1) having the above unit (u1) and a resin (A2-2) having the above unit (u2).
[0037] <Resin (A2-1)> The "resin (A2-1) having unit (u1)" constituting the mixed resin (A2) refers to a resin (A2-1) in which the ratio of the radical polymerizable monomer (a1) to the total monomers constituting the resin (A2-1) is 0.5 mol% or more. The radical polymerizable monomer (a1) is as described above. The resin (A2-1) may be composed of one type of resin or may be composed of multiple types of resins.
[0038] The repeating unit of the resin (A2-1) may be the above-mentioned unit (u1), or may have other units in addition to the above-mentioned unit (u1). Examples of other units include the above-mentioned unit (u2) and unit (u3). In one embodiment, the ratio of the radical polymerizable monomer (a1) to the total monomers constituting the resin (A2-1) may be 0.5 mol% or more and 50 mol% or less, or 10 mol% or more and 30 mol% or less, the ratio of the radical polymerizable monomer (a2) to the total monomers constituting the resin (A2-1) may be 1 mol% or more and 10 mol% or less, or 2 mol% or more and 5 mol% or less, and the ratio of the radical polymerizable monomer (a3) to the total monomers constituting the resin (A2-1) may be 49 mol% or more and 98.5 mol% or less, or 65 mol% or more and 88 mol% or less.
[0039] <Resin (A2-2)> The "resin (A2-2) having unit (u2)" constituting the mixed resin (A2) refers to a resin in which the proportion of monomer (a2) in the total monomers constituting the resin (A2-2) is 1 mol % or more. The monomer (a2) is as described above. The resin (A2-2) may be composed of one type of resin or may be composed of multiple types of resins.
[0040] The repeating unit of the resin (A2-2) may be the above-mentioned unit (u2), or may have other units in addition to the above-mentioned unit (u2). Examples of other units include the above-mentioned unit (u1) and unit (u3). In one embodiment, the ratio of the radical polymerizable monomer (a1) to the total monomers constituting the resin (A2-2) may be 0 mol% or more and 50 mol% or less, or 0 mol% or more and 30 mol% or less, the ratio of the radical polymerizable monomer (a2) to the total monomers constituting the resin (A2-2) may be 1 mol% or more and 10 mol% or less, or 2 mol% or more and 5 mol% or less, and the ratio of the radical polymerizable monomer (a3) to the total monomers constituting the resin (A2-2) may be 49 mol% or more and 98.5 mol% or less, or 65 mol% or more and 88 mol% or less.
[0041] <Mixing ratio> In the mixed resin (A2), the ratio of the resin (A2-1) having the unit (u1) and the resin (A2-2) having the unit (u2) may be such that the aromatic ring ratio described below is satisfied for the entire resin (A). In one embodiment, the ratio of the resin (A2-1) to the total of the resin (A2-1) and the resin (A2-2) may be 1% by mass or more and 99% by mass or less, 30% by mass or more and 99% by mass or less, 50% by mass or more and 99% by mass or less, or 70% by mass or more and 99% by mass or less. Alternatively, in one embodiment, the ratio of the resin (A2-2) to the total of the resin (A2-1) and the resin (A2-2) may be 1% by mass or more and 99% by mass or less, 30% by mass or more and 99% by mass or less, 50% by mass or more and 99% by mass or less, or 70% by mass or more and 99% by mass or less.
[0042] <Preferable combination of mixed resin (A2)> In particular, when the mixed resin (A2) is a combination of the following resin (A2-1) and resin (A2-2), more excellent effects are likely to be exhibited. Resin (A2-1): Contains unit (u1) as well as one or both of unit (u2) and unit (u3), particularly both unit (u2) and unit (u3). The ratio of each unit may be, for example, as described above. Resin (A2-2): Contains units (u2) and (u3), but does not contain units (u1). The ratio of each unit may be, for example, as described above.
[0043] 1.1.3 Aromatic ring ratio Resin (A) has an aromatic ring ratio of 0.5% to 30%. The "aromatic ring ratio" refers to the ratio by weight (W t Weight of aromatic rings (W a ) and (W a / W t )×100(%). The aromatic ring ratio of the resin (A) contained in the coating agent can be specified by various analytical devices. For example, a spectrophotometer (UV-Vis Lambda650S, manufactured by PerkinElmer) is used to measure the absorption spectrum of the aromatic ring observed around 250 nm, and the amount is quantified from the absorption intensity. Alternatively, for example, the aromatic ring ratio of the resin (A) can be specified from the charge ratio of the monomers constituting the resin (A) during the production stage of the resin (A). According to the knowledge of the present inventor, the aromatic ring ratio of the resin (A) contained in the coating agent affects the windproof property (breathability) imparted by the coating agent film to the water-repellent fiber fabric. If the aromatic ring ratio of the resin (A) is too low, the windproof property (breathability) is deteriorated, and the coating agent film tends to peel off easily. On the other hand, if the aromatic ring ratio of the resin (A) is too high, the glass transition temperature Tg of the resin (A) may become excessively high, which may impair the texture. If the aromatic ring ratio of the resin (A) is 0.5% or more and 30% or less, excellent windproofness (for example, windproofness after washing) is exhibited, the coating agent film is difficult to peel off, and the texture is likely to be excellent. The aromatic ring ratio of the resin (A) is preferably 5% or more and 20% or less, more preferably 5% or more and 10% or less.
[0044] As described above, the resin (A) may be a copolymer resin (A1), a mixed resin (A2), or a combination thereof. The resin (A) may consist of one type of resin, or may consist of multiple types of resin. When the resin (A) consists of multiple types of resin, the aromatic ring ratio of the resin (A) can be calculated (weighted average) based on the aromatic ring ratio of each of the multiple types of resin and the composition ratio of the multiple types of resin.
[0045] 1.1.4 Glass transition temperature The glass transition temperature Tg of the resin (A) is preferably -40°C or higher and 0°C or lower, more preferably -40°C or higher and -10°C or lower, and even more preferably -40°C or higher and -20°C or lower. If the glass transition temperature Tg of the resin (A) is too low, the tackiness (stickiness) of the coating surface may become excessively strong, and if the glass transition temperature Tg is too high, the texture may become too hard. The glass transition temperature Tg of the resin (A) may be determined, for example, by actual measurement, or may be determined by calculation based on the glass transition temperatures and composition ratios of the monomers constituting the resin (A).
[0046] 1.1.5 Acid number The acid value (mgKOH) of the resin (A) is preferably 1 to 20, more preferably 5 to 15, and even more preferably 5 to 10. If the acid value of the resin (A) is too low, stable emulsification may not be obtained during emulsion dispersion polymerization, and if the acid value of the resin (A) is too high, washing resistance may be poor. The acid value of the resin (A) is measured in accordance with the neutralization titration method of JIS K 0070 (1992), 3.1, using a mixed solvent of acetone:water = 10:1 (volume ratio) as the measurement solvent, and dissolving 1 g of the sample in 60 mL of this mixed solvent.
[0047] 1.1.6 Manufacturing method of resin (A) Resin (A) can be synthesized, for example, as follows: However, the method described below is merely one example, and resin (A) can also be synthesized by other methods.
[0048] Resin (A) can be obtained by emulsion dispersion polymerization of monomer (a1), monomer (a2) and optional monomer (a3) in the above-mentioned mass ratio in the presence of water, a surfactant, an emulsifying dispersant, 0.01 to 5 mass parts of a chain transfer agent (per 100 mass parts of the total of monomers), a polymerization initiator, etc. In the present disclosure, emulsification and dispersion are collectively referred to as emulsion dispersion.
[0049] In the emulsion dispersion polymerization, an organic solvent may be used in addition to water as a solvent, depending on the case. Examples of such organic solvents include glycols such as ethylene glycol, diethylene glycol, butyl glycol, and butyl diglycol; and alcohols such as methanol, ethanol, and isopropanol.
[0050] In the emulsion dispersion polymerization, a commonly used known non-reactive surfactant such as a nonionic, anionic, cationic or amphoteric surfactant, or a reactive surfactant having a polymerizable group such as a vinyl group or an allyl group can be used. The surfactant can be used alone or in combination of two or more kinds.
[0051] The content of the surfactant is preferably in the range of 0.1 to 10 parts by mass per 100 parts by mass of the total of the monomers. The total concentration of the monomers in the emulsion during the preparation of the resin (A) (resin content) is preferably 30 to 60% by mass.
[0052] Examples of nonionic surfactants include alkylene oxide adducts of linear or branched alcohols or alkenols having 8 to 24 carbon atoms, alkylene oxide adducts of monocyclic or polycyclic phenols, alkylene oxide adducts of linear or branched aliphatic amines having 8 to 44 carbon atoms, alkylene oxide adducts of linear or branched fatty acid amides having 8 to 44 carbon atoms, alkylene oxide adducts of linear or branched fatty acids having 8 to 24 carbon atoms, reaction products of polyhydric alcohols, linear or branched fatty acids having 8 to 24 carbon atoms, and alkylene oxides, and alkylene oxide adducts of fats and oils.
[0053] Examples of the anionic surfactant include sulfate salts, phosphate salts, carboxylate salts, and sulfosuccinate-type anionic surfactants of the nonionic surfactants, sulfate salts and phosphate salts of higher alcohols, sulfonates of fats and oils, alkylbenzenesulfonates, alkylnaphthalenesulfonates, and formalin condensates of naphthalenesulfonates.
[0054] Examples of cationic surfactants include aliphatic amine salts and their quaternary ammonium salts, and aromatic quaternary ammonium salts. Examples of amphoteric surfactants include carboxybetaine, sulfobetaine, aminocarboxylates, and imidazoline derivatives.
[0055] Among these, from the viewpoints of emulsification dispersibility and stability, at least one selected from the group consisting of alkylene oxide adducts of linear or branched alcohols having 8 to 24 carbon atoms, alkylene oxide adducts of monocyclic or polycyclic phenols, and anionized products thereof is preferred.
[0056] As the monocyclic or polycyclic phenol, a (3 to 8 mol) styrene adduct, (3 to 8 mol) α-methylstyrene adduct, or (3 to 8 mol) benzyl chloride reaction product of phenol, 4-cumylphenol, 4-phenylphenol, or 2-naphthol is preferred.
[0057] The chain transfer agent is not particularly limited, and may be, for example, a mercaptan-based compound or an alcohol. Examples of the mercaptan-based compound include n-hexyl mercaptan, n-octyl mercaptan, t-octyl mercaptan, n-decyl mercaptan, n-dodecyl mercaptan, and t-dodecyl mercaptan. The mercaptan-based compound also includes mercapto group-containing alcohols such as mercaptoethanol and mercaptopropanol. Examples of the alcohol include aliphatic alcohols of about C1 to C6 such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, and n-butyl alcohol, and aromatic alcohols of about C7 to C13 such as benzyl alcohol. Other chain transfer agents include α-methylstyrene dimer. The chain transfer agent may be used alone or in combination of two or more. A chain transfer agent having a mercapto group is preferred. The polymerization initiator is not particularly limited, but known initiators that are usually used in emulsion dispersion polymerization of acrylic resins can be used. For example, as a water-soluble polymerization initiator, persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate, hydrogen peroxide, and the like can be used alone or in combination. As an oil-soluble polymerization initiator, one or more of peroxides such as benzoyl peroxide and lauroyl peroxide, azobis compounds such as azobisisobutyronitrile and azobisvaleronitrile, and polymeric azo polymerization initiators can be used in combination. A water-soluble polymerization initiator and an oil-soluble polymerization initiator can also be used in combination. In addition, a redox initiator consisting of a combination of the above-mentioned peroxide and a reducing agent such as sodium hydrogen sulfite, sodium thiosulfate, Rongalite, and ascorbic acid can also be used.
[0058] The emulsion dispersion polymerization can be carried out by heating the monomer mixture in an aqueous liquid under stirring in the presence of a chain transfer agent, a polymerization initiator, an emulsifying dispersant, etc. as necessary. The reaction temperature is, for example, about 30 to 100°C, and the reaction time is, for example, about 1 to 10 hours. The reaction temperature can be adjusted by adding the monomer mixture or the monomer emulsion dispersion all at once or gradually dropping it into a reaction vessel containing water and a polymerization initiator.
[0059] As the emulsion dispersion polymerization method, any polymerization method can be used, such as the usual one-stage continuous uniform monomer dropping method, the core-shell polymerization method which is a multi-stage monomer feed method, or the power feed polymerization method which continuously changes the monomer composition fed during polymerization.
[0060] From the viewpoint of maintaining a more stable emulsifiability of the acrylic resin emulsion, it is preferable to adjust the content of the resin (A) in the emulsion dispersion to 40 to 60 mass % and the pH of the emulsion dispersion to 6.0 to 9.0. The pH may be adjusted before, during, or after the polymerization reaction.
[0061] 1.2 Polyvalent metal salts (B) The polyvalent metal salt (B) is a salt containing a polyvalent metal ion having a valence of 2 or more. The polyvalent metal salt (B) may be used alone or in combination of two or more.
[0062] The polyvalent metal ion that constitutes the polyvalent metal salt (B) is Ca 2+ , Cu 2+ , Ni 2+ , Mg 2+ , Sr 2+ , Zn 2+ , B.A. 2+ , Al 3+ , Fe 3+ , Cr 3+ , Co 3+ , Fe 2+ , La 3+ , Nd 3+ , Y 3+ and Zr 4+ At least one selected from the following is preferred, and Ca 2+ It is preferable that:
[0063] The anion constituting the polyvalent metal salt (B) is, for example, NO 3- , Cl - , I - , Br - , ClO 3- , C.H. 3 COO - and S.O. 4 2- From the viewpoint of the solubility of the salt, etc., NO 3- and S.O. 4 2- It is particularly preferred that the compound is one or both of the following:
[0064] 1.3 Amount of polyvalent metal salt (B) relative to resin (A) By using the resin (A) and the polyvalent metal salt (B) in combination in the coating agent, a coating agent film having better washing durability (windproofness after washing) can be obtained. The amount of polyvalent metal salt (B) added to the resin (A) is not particularly limited. For example, when the ratio of the mass of the polyvalent metal salt (B) to the mass of the unit (u2) constituting the resin (A) is 1.0% or more and 10.0% or less, a better effect is easily obtained. If the amount of the polyvalent metal salt (B) added is too large, the coating agent film may become white and embrittled, and peeling may become more likely. If the amount of the polyvalent metal salt (B) added is too small, peeling and tack (stickiness of the coating film surface) of the coating agent film may become more likely. The ratio of the mass of the polyvalent metal salt (B) to the mass of the unit (u2) constituting the resin (A) may be 1.5% or more and 9.5% or less, or 2.0% or more and 9.0% or less.
[0065] 1.4 Other The coating agent may be composed of the above-mentioned resin (A) and polyvalent metal salt (B), or may contain other components (C) together with the resin (A) and polyvalent metal salt (B). Examples of other components (C) include thickeners, resins other than the resin (A), salts other than the polyvalent metal salt (B), and various additives described below. The coating agent may contain 49.998% by mass or more and 99.998% by mass or less of the resin (A) in a state in which the solvent has been removed (a state in which the coating agent film is formed after drying). The coating agent may also contain 20 ppm or more and 30,000 ppm or less of the polyvalent metal salt (B) in a state in which the solvent has been removed. The coating agent may also contain 0% by mass or more and 50% by mass or less of the above-mentioned other components (C) other than the solvent in a state in which the solvent has been removed. In one embodiment, it is preferable to add 100 ppm to 2000 ppm of polyvalent metal salt (B) to a coating agent containing 10% by mass to 50% by mass, preferably 30% by mass to 50% by mass, of resin (A) in a dry state after removing the solvent. The coating agent can be easily obtained by mixing the above-mentioned components. For example, the coating agent may be obtained by dispersing resin (A) and dispersing or dissolving polyvalent metal salt in a solvent such as water.
[0066] The coating agent may contain a thickener. The thickener adjusts the viscosity and stickiness of the coating agent and adjusts the coatability of the coating agent to the fiber fabric. One or more types of thickeners may be used. The blending amount of the thickener may be appropriately set according to the processing suitability of the coating machine. The thickener may be at least one selected from natural organic polymers such as gum arabic, tragacanth gum, guar gum, locust bean gum, sodium alginate, carrageenan, xanthan gum, and pullulan; semi-synthetic organic polymers such as methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and carboxymethyl cellulose; and synthetic organic polymers such as polyvinyl alcohol, polyether polyol type polyurethane resin, alkali thickening type acrylic resin, ethylene oxide higher fatty acid ester, and polyethylene oxide.
[0067] From the viewpoint of water repellency and waterproofness, the thickener is preferably water-insoluble. Examples of water-insoluble thickeners include alkali thickening type acrylic resins, polyether polyol type polyurethane resins, and combinations thereof.
[0068] The alkali-thickening acrylic resin may be used alone or in combination of two or more. Some alkali-thickening acrylic resins fall under the category of the resin (A2-2) above. In this case, the alkali-thickening acrylic resin may be combined with the resin (A2-1) above so that a predetermined aromatic ring ratio is satisfied, to become the mixed resin (A2). In the coating agent, when the alkali-thickening acrylic resin falls under the category of the resin (A2-2) and is combined with the resin (A2-1) above to become the mixed resin (A2) having a predetermined aromatic ring ratio, the alkali-thickening acrylic resin is calculated as the resin (A2-2) above, not as the other component (C). The alkali-thickening acrylic resin is preferably used in an emulsified and dispersed state, for example. As the alkali-thickening acrylic resin, commercially available products can be used, such as Nikasol VT-253A (manufactured by Nippon Carbide Industries Co., Ltd.), Aron A-20P, Aron A-7150, Aron A-7070, Aron B-300, Aron B-300K, Aron B-500 (all manufactured by Toagosei Co., Ltd.), Julimer AC-10LHP, Julimer AC-10SHP, Rheogic 250H, Rheogic 835H, Junron PW-110, and Junron P. Examples of such antibacterial agents include Primal W-150 (all manufactured by Nippon Junyaku Co., Ltd.), Primal ASE-60, Primal TT-615, Primal RM-5 (all manufactured by Rohm and Haas Japan Co., Ltd.), SN Thickener A-818, SN Thickener A-850 (all manufactured by San Nopco Co., Ltd.), Paragum 500 (manufactured by Para-Chem Southern Co., Ltd.), Rheolate 430 (manufactured by Elementis Japan Co., Ltd.), and Neosticker V-420 (manufactured by Nicca Chemical Co., Ltd.).
[0069] In order to adjust the coatability of the coating agent, a polyurethane resin can be used in combination with the alkali-thickening acrylic resin. The polyurethane resin can be used in an amount of 0.3% by mass or more and 1% by mass or less based on the coating agent.
[0070] The polyurethane resin that can be used in combination with the alkali thickening acrylic resin can be nonionic polyether polyol urethane polymer.As such polyether polyol urethane polymer, commercially available products can be used, such as Adekanol UH-420, Adekanol UH-450, Adekanol UH-540, Adekanol UH-752 (all manufactured by Asahi Denka Kogyo Co., Ltd.), SN Thickener 601, SN Thickener 612, SN Thickener 621N, SN Thickener 623N (all manufactured by San Nopco Co., Ltd.), Rheolate 244, Rheolate 278, Rheolate 300 (all manufactured by Elementis Japan Co., Ltd.), DK Thickener SCT-275 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).
[0071] 2.Laminated fiber fabric The laminated fiber fabric of the present disclosure comprises a fiber fabric, a water-repellent coating, and a coating agent coating. The water-repellent coating contains a non-fluorinated water-repellent agent. The water-repellent coating is formed on at least a portion of the fiber fabric. The coating agent coating is formed on one side of the fiber fabric. The coating agent coating is formed on at least a portion of a surface of the water-repellent coating. The coating agent coating is made of the coating agent of the present disclosure.
[0072] 2.1 Textile fabrics The fibers constituting the fiber fabric are not particularly limited, and may be chemical fibers such as polyester, nylon, acrylic, polyurethane, rayon (acetate, viscose, etc.), polylactic acid, aromatic polyamide, polyimide, polyphenylene sulfide, etc., natural fibers such as cotton, hemp, silk, wool, etc., or blends, mixed spinning, interwoven, or interknitted products of these materials. The fiber fabric may be in any form, such as woven fabric, knitted fabric, or nonwoven fabric.
[0073] The fiber fabric may be a thin woven fabric in which the coating agent (resin liquid) is particularly likely to penetrate to the back surface of the fiber fabric (the surface opposite to the surface to which the resin liquid is applied), or a knitted fabric in which gaps are more likely to form between the threads than in a woven fabric. Even when such a fiber fabric is used, it is possible to prevent the resin liquid from penetrating to the back surface of the fiber fabric (stripping through), and to form a coating agent film having windproof properties, etc., on the fiber fabric.
[0074] The fibers constituting the fiber fabric may be long fibers, short fibers, or a combination thereof. The yarn using the fibers may be raw silk, twisted yarn, textured yarn, or a combination thereof. The textured yarn is not particularly limited, and may be at least one selected from false twist textured yarn (woolly textured yarn, DTY, improved false twist textured yarn, etc.), push textured yarn, shaping textured yarn, abrasion textured yarn, Taslan textured yarn, yarn length difference uniform textured yarn, composite textured yarn, fluff textured yarn, intertwined bundled yarn, intertwined blended yarn, etc. From the viewpoint of preventing the coating agent from penetrating (stripping through) into the fiber fabric, it is preferable to use textured yarn.
[0075] The cross-sectional shape of the fiber is not particularly limited, and may be any shape such as round, triangular, star-shaped, flat, C-shaped, hollow, well-shaped, dog-bone, etc. From the viewpoint of preventing the coating agent from penetrating (stripping through) into the fiber fabric, it is preferable that the cross-sectional shape of the fiber is at least one shape selected from triangular, star-shaped, flat, dog-bone, etc. (it is a modified cross-section yarn).
[0076] The fiber fabric may be colored in advance or may not be colored. The fiber fabric may be colored with a dye such as a disperse dye, a cationic dye, an acid dye, a direct dye, a reactive dye, a vat dye, or a sulfide dye, or a fluorescent whitening agent, or a pigment, or the like. The material used to color the fiber fabric is not particularly limited, and may be selected according to the material of the fiber fabric, etc. The coloring method is not particularly limited, and may be a method such as original dyeing, dip dyeing, or printing.
[0077] The fiber fabric may be one that has been subjected to flame retardant treatment, antistatic treatment, antibacterial and deodorizing treatment, antibacterial treatment, ultraviolet shielding treatment, light resistance improving treatment, water absorption treatment, or the like.
[0078] 2.2 Water-repellent coating The water-repellent coating contains a non-fluorine-based water repellent. The non-fluorine-based water repellent may be one or both of a hydrocarbon-based compound and a silicone-based compound. From the viewpoint of flexibility of the fiber fabric, it is preferable that the non-fluorine-based water repellent contains a silicone-based compound. The non-fluorine-based water repellent may be a silicone-based compound alone or a mixture of a silicone-based compound and a hydrocarbon-based compound. The water-repellent coating may or may not contain other water-repellent components together with the non-fluorine-based water repellent. The water-repellent coating may contain 50% by mass or more and 100% by mass or less of the non-fluorine-based water repellent, or 60% by mass or more and 100% by mass or less of the non-fluorine-based water repellent.
[0079] 2.2.1 Hydrocarbon compounds The hydrocarbon-based compound is not particularly limited as long as it is capable of forming a water-repellent coating, and examples thereof include those disclosed in JP2015-120895A, JP2015-120894A, JP2015-120893A, JP2014-1252A, JP2006-328624A, JP2015-40365A, JP2015-3445A, etc.
[0080] Specifically, the hydrocarbon compound may be at least one selected from aliphatic hydrocarbons, aliphatic carboxylic acids, polyolefins, polyacrylic esters, polymethacrylic esters, and the like.
[0081] The aliphatic hydrocarbon may be, for example, one or both of a paraffinic hydrocarbon and an olefinic hydrocarbon.
[0082] The aliphatic carboxylic acid may be, for example, a saturated or unsaturated aliphatic carboxylic acid, or an ester compound of an aliphatic carboxylic acid. The number of carbon atoms of the aliphatic carboxylic acid is preferably, for example, 12 or more.
[0083] The polyolefin may be, for example, at least one selected from polyethylene, polypropylene, and an ethylene-propylene copolymer.
[0084] The polyacrylic acid ester and polymethacrylic acid ester to be used may have a carbon number of 12 or more and 24 or less in the hydrocarbon present via an ester bond. In this case, the hydrocarbon may be linear or branched, may be a saturated or unsaturated hydrocarbon, and may have an alicyclic or aromatic ring. Among these, linear ones are preferred, and linear alkyl groups are more preferred.
[0085] As these hydrocarbon compounds, NR-158 (manufactured by Nicca Chemical Co., Ltd.), TH-44 (manufactured by Nicca Chemical Co., Ltd.), PW-182 (manufactured by Daiwa Chemical Co., Ltd.), Fabol RSH (manufactured by Huntsman Japan Co., Ltd.), Palladium ECO-500 (manufactured by Ohara Palladium Chemical Co., Ltd.), Palladium ECO-85A (manufactured by Ohara Palladium Chemical Co., Ltd.), NX018 (manufactured by Nanotex Co., Ltd.), Mayseed P-300C (manufactured by Meisei Chemical Co., Ltd.), NT-X028 (manufactured by Nanotex, LLC.), miDorievoPelNF (manufactured by Beyond Surface Technologies AG), XF-5001 (manufactured by Daikin Industries, Ltd.), etc. are commercially available. In addition, as a product containing a poly(meth)acrylic acid ester compound, NEOSEED NR-158 (manufactured by Nicca Chemical Co., Ltd.) etc. are commercially available.
[0086] 2.2.2 Silicone compounds The silicone compound may be an organo-modified silicone represented by the following formula (S1). The silicone compound may be used alone or in combination of two or more. In the following formula (S1), the structural units may be arranged in blocks, randomly, or alternately.
[0087] [ka] [In formula (S1), R 20 , R 21 and R 22 are each independently a hydrogen atom, a methyl group, an ethyl group, or an alkoxy group having 1 to 4 carbon atoms; R 23 is a hydrocarbon group having 8 to 40 carbon atoms and an aromatic ring, or an alkyl group having 8 to 40 carbon atoms, R 30 , R 31 , R 32 , R 33 , R 34 and R 35 are each independently a hydrogen atom, a methyl group, an ethyl group, an alkoxy group having 1 to 4 carbon atoms, a hydrocarbon group having 8 to 40 carbon atoms and an aromatic ring, or an alkyl group having 3 to 22 carbon atoms; a is an integer of 0 or more, b is an integer of 1 or more, (a+b) is 10 to 200; when a is 2 or more, a plurality of R 20 and R 21 may be the same or different, and when b is 2 or more, there are multiple R 22 and R 23 may be the same or different.]
[0088] R is easy to manufacture industrially and is readily available. 20 , R 21 and R 22 are each independently preferably a hydrogen atom or a methyl group, and more preferably a methyl group.
[0089] As the above-mentioned hydrocarbon group having 8 to 40 carbon atoms and an aromatic ring, one or both of a phenylethyl group and a phenylpropyl group are preferred in terms of ease of industrial production and availability.
[0090] The alkyl group having 8 to 40 carbon atoms is preferably an alkyl group having 12 to 36 carbon atoms, more preferably an alkyl group having 16 to 34 carbon atoms, in terms of preventing the coating agent from striking through. The fewer the carbon atoms in the alkyl group, the more the flexibility of the laminated fiber fabric tends to be excellent. Also, the greater the carbon number in the alkyl group, the more likely it is that strike-through can be prevented. If the carbon number exceeds 40, the stability of the water repellent agent tends to decrease. Furthermore, if the carbon number is less than 8, strike-through tends to occur easily.
[0091] Among organo-modified silicones, R is favored because it is easy to manufacture industrially and is readily available. 30 , R 31 , R 32 , R 33 , R 34 and R 35 are each independently preferably a hydrogen atom, a methyl group, an ethyl group, or an alkoxy group having 1 to 4 carbon atoms, and more preferably a methyl group.
[0092] In the organo-modified silicone, a is an integer of equal to or greater than 0. In terms of ease of industrial production, ease of availability, and superior peel strength, a is preferably equal to or less than 40, and more preferably equal to or less than 30.
[0093] In the organo-modified silicone, (a+b) is 10 to 200. From the viewpoint of ease of industrial production and availability, (a+b) is preferably 20 to 100, and more preferably 40 to 60. When (a+b) is within the above range, the silicone itself tends to be easier to produce and handle.
[0094] Specific examples of silicone compounds include Gelanex SH (manufactured by Matsumoto Oil Co., Ltd.), Drypon 600E (manufactured by Nicca Chemical Co., Ltd.), Poron MR (manufactured by Shin-Etsu Chemical Co., Ltd.), and Poron MF-49 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0095] The silicone compound may be, for example, at least one of a silicone resin and a silicone oil. In this case, the silicone compound may be used alone or in combination of two or more kinds.
[0096] The silicone resin may be an organopolysiloxane containing MQ, MDQ, MT, MTQ, MDT or MDTQ as a component, being solid at 25° C., and having a three-dimensional structure, where M, D, T and Q are each (R″) 3 SiO 0.5 Units, (R'') 2 SiO unit, R''SiO 1.5 Units and SiO 2 R″ represents a monovalent aliphatic hydrocarbon group having 1 to 10 carbon atoms, or a monovalent aromatic hydrocarbon group having 6 to 15 carbon atoms.
[0097] Silicone resins are commonly known as MQ resins, MT resins or MDT resins, and may have moieties designated as MDQ, MTQ or MDTQ.
[0098] Silicone resins are also available as solutions in suitable solvents, such as relatively low molecular weight methylpolysiloxanes, decamethylcyclopentasiloxane, octamethylcyclotetrasiloxane, n-hexane, isopropyl alcohol, methylene chloride, 1,1,1-trichloroethane, and mixtures of these solvents.
[0099] Examples of silicone resin solutions include KF7312J (a 50:50 mixture of trimethylsilyl-containing polysiloxane:decamethylcyclopentasiloxane), KF7312F (a 50:50 mixture of trimethylsilyl-containing polysiloxane:octamethylcyclotetrasiloxane), KF9021L (a 50:50 mixture of trimethylsilyl-containing polysiloxane:low-viscosity methylpolysiloxane), and KF7312L (a 50:50 mixture of trimethylsilyl-containing polysiloxane:low-viscosity methylpolysiloxane), all of which are commercially available from Shin-Etsu Chemical Co., Ltd.
[0100] Examples of silicone resins alone include MQ-1600 solid Resin (trimethylsilyl group-containing polysiloxane) and MQ-1640 Flake Resin (trimethylsilyl group-containing polysiloxane, polypropylsilsesquioxane), both of which are commercially available from Toray Dow Corning Co., Ltd. The above commercially available products contain trimethylsilyl group-containing polysiloxane, and include MQ, MDQ, MT, MTQ, MDT, or MDTQ.
[0101] Silicone oil is a linear organopolysiloxane, and may have organic group at least in either the side chain or end of organopolysiloxane.As such silicone oil, the same thing as hydrophobized silicone oil and functionalized silicone oil can be used, and for example, straight silicone oil such as dimethyl silicone oil, methylphenyl silicone oil, methylhydrogen silicone oil; modified silicone oil such as amino modified silicone oil, epoxy modified silicone oil, carbinol modified silicone oil, mercapto modified silicone oil, carboxyl modified silicone oil, polyether modified silicone oil, alkyl modified silicone oil, aralkyl modified silicone oil, alkylaralkyl modified silicone oil, higher fatty acid ester modified silicone oil, higher aliphatic amide modified silicone oil, etc. can be mentioned.
[0102] The amino-modified silicone oil may be a compound having an organic group containing an amino group and / or an imino group at least on the side chain or the end of the organopolysiloxane. Such an organic group may be, for example, -R-NH 2 an organic group represented by the formula: -R-NH-R'-NH 2Examples of R and R' include divalent groups such as an ethylene group and a propylene group. A part or all of the amino group and / or imino group may be a blocked amino group and / or imino group. The blocked amino group and / or imino group can be obtained, for example, by treating the amino group and / or imino group with a blocking agent. Examples of the blocking agent include fatty acids having 2 to 22 carbon atoms, acid anhydrides of fatty acids having 2 to 22 carbon atoms, acid halides of fatty acids having 2 to 22 carbon atoms, and aliphatic monoisocyanates having 1 to 22 carbon atoms.
[0103] The functional group equivalent of the amino-modified silicone oil is preferably from 100 to 20,000 g / mol, more preferably from 150 to 12,000 g / mol, and still more preferably from 200 to 4,000 g / mol, from the viewpoint of water repellency.
[0104] The amino-modified silicone oil is preferably liquid at 25° C. The kinetic viscosity of the amino-modified silicone oil at 25° C. is 10 to 100,000 mm 2 / s is preferably 10 to 30,000 mm 2 / s is more preferable, and 10 to 5,000 mm 2 More preferably, the kinematic viscosity at 25°C is 100,000 mm 2 If it is greater than 1 / s, the viscosity will be too high and workability will tend to be poor. The kinematic viscosity at 25°C refers to the value measured by the method described in JIS K2283:2000 (Ubbelohde viscometer).
[0105] Amino-modified silicone oils can be easily obtained as commercial products. Examples of commercial products include KF8005, KF-868, KF-864, KF-393, KF-8021 (all of which are trade names of Shin-Etsu Chemical Co., Ltd.), TSF-4709, XF42-B1989 (all of which are trade names of Momentive Performance Materials Japan Co., Ltd.), BY16-872, SF-8417, BY16-853U, BY16-892 (all of which are trade names of Dow Corning Toray Co., Ltd.), KF-8010 (Shin-Etsu Chemical Co., Ltd.), and WACKER (registered trademark) FINISH WR 301 (manufactured by Asahi Kasei Wacker Silicone).
[0106] Silicone oils other than amino-modified silicone oils are also easily available as commercially available products. Examples of commercially available products include KF-101 (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: epoxy-modified silicone oil), X-22-3701E (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: carboxyl-modified silicone oil), SF8428 (manufactured by Dow Corning Toray Co., Ltd., trade name: carbinol-modified silicone oil), KF-9901 (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: methyl hydrogen silicone oil), and X-22-715 (manufactured by Shin-Etsu Chemical Co., Ltd., trade name: methyl hydrogen silicone oil). , higher fatty acid ester modified silicone oil), KF-96-3000cp (manufactured by Shin-Etsu Chemical Co., Ltd., trade name, dimethyl silicone oil), SF8416 (manufactured by Dow Corning Toray Co., Ltd., trade name, alkyl modified silicone oil), SH203 (manufactured by Dow Corning Toray Co., Ltd., trade name, alkyl aralkyl modified silicone oil), SF8410 (manufactured by Dow Corning Toray Co., Ltd., trade name, polyether modified silicone oil).
[0107] 2.2.3 Other ingredients The water-repellent coating may contain various additives, such as inorganic fine particles such as silica to prevent seam slippage and snagging, softeners such as silicone, and antistatic agents such as guanidine hydrochloride, higher alcohol sulfate ester salts, amine salts, polyethylene glycol-type and betaine-type surfactants.
[0108] 2.2.4 Thickness and position of water-repellent coating The water-repellent coating is formed on at least a part of the fiber fabric. The water-repellent coating may be formed on the surface of the fiber fabric. In addition, the water-repellent resin may accumulate in a part between the yarns of the fibers constituting the fiber fabric, and such a part may exist in this embodiment. The thickness of the water-repellent coating formed on the fiber fabric may be, for example, 1 μm or less, preferably 100 nm or less, more preferably 10 nm or less. When the thickness of the water-repellent coating is 100 nm or less, it may be difficult to confirm the water-repellent coating. In this case, when a water-repellent test is performed on the fiber fabric, if the fiber fabric has water repellency and the water repellency is grade 3 or higher, the fiber fabric is deemed to have a water-repellent coating formed thereon.
[0109] The water-repellent coating may be attached to at least a part of the surface of the fibers (yarns) constituting the fiber fabric, or may be attached to the entire surface of the fibers (yarns) constituting the fiber fabric. Furthermore, the water-repellent coating may be attached to the fibers (yarns) constituting the fiber fabric so as to be dotted thereon.
[0110] 2.3 Coating film The coating agent film can impart excellent wind resistance to the fiber fabric. The coating agent film can also contribute to preventing padding from falling out and waterproofing. The coating agent film is formed on one side of the fiber fabric. The coating agent film is also formed on at least a part of the surface of the water-repellent film. The coating agent film is made of the coating agent of the present disclosure.
[0111] The coating agent constituting the coating agent film is as described above. That is, the coating agent film contains the above-mentioned resin (A), polyvalent metal salt (B), and other optional components. The ratio of each component is as described above. The coating agent film may contain various additives such as ultraviolet absorbers, antioxidants, crosslinking agents, catalysts, deodorants, antibacterial agents, flame retardants, other water repellents, water resistance improvers such as silicon dioxide, pigments, and infrared absorbers.
[0112] The coating agent film may be porous or non-porous. When not only windproofness but also breathability is required, the coating agent film in the laminated fiber fabric may be a porous film, or there may be a portion on one side of the laminated fiber fabric where the coating agent film is not present. Examples of the portion where the coating agent film is not present include all or a portion of a convex portion where warp and weft yarns overlap in a woven fabric or a convex portion where loops of a knitted fabric overlap, or through holes formed in the coating agent film. The laminated fiber fabric may have a portion where the coating agent film is not formed on the surface where the coating agent film is formed, such as a convex portion where warp and weft yarns overlap in a woven fabric or a convex portion where loops of a knitted fabric overlap.
[0113] The thickness of the coating agent film may be appropriately determined depending on the desired windproofness, etc. From the viewpoint of texture in addition to windproofness, the thickness of the coating agent film may be 500 μm or less, preferably 300 μm or less, and more preferably 100 μm or less.
[0114] The laminated fiber fabric has a coating agent film on one side of the fiber fabric. On the other side of the laminated fiber fabric, the fiber fabric may form the outermost surface. Incidentally, even on the side on which the fiber fabric forms the outermost surface, the resin constituting the coating agent film may be present at the boundary between the yarns, etc. The laminated fiber fabric preferably has a coating agent film formed only on one side of the laminated fiber fabric, and the resin constituting the coating agent film is not present on the side on which the fiber fabric forms the outermost surface.
[0115] 2.4 Water repellency The water repellency of the laminated fiber fabric may be, for example, grade 3 or higher, preferably grade 4 or higher, and more preferably grade 5, in the JIS L1092 water repellency test (spray test). If the water repellency is grade 3 or higher, a coating agent film can be more easily attached to one side of the fiber fabric. In addition, even when a fiber product or the like is produced using the laminated fiber fabric, wetting of the fabric can be suppressed due to the excellent water repellency.
[0116] 2.5 Breathability The air permeability of the laminated fiber fabric is 1 cm when tested according to JIS L1096:2010 A method (Fragile type method). 3 / cm 2 The laminated fiber fabric may have a durable air permeability of 2 cm 3 / cm 2 ·s or less. The term "durable air permeability" refers to the air permeability after the laminated fiber fabric has been washed 10 times in accordance with JIS L0217 103. The washing process is performed 5 times with a washing time of 25 minutes and a rinsing time of 10 minutes, and this process is repeated to complete 10 washing processes. The fabric is hung to dry once after the 10 washing processes.
[0117] When the laminated fiber fabric needs to be waterproof, the water pressure resistance of the laminated fiber fabric may be 250 mm or more, preferably 350 mm or more, more preferably 1000 mm or more, and even more preferably 2000 mm or more, when measured, for example, by JIS L1092 Water Resistance Test (Hydrostatic Pressure Method) Method A (low water pressure method). A laminated fiber fabric having a water pressure resistance of 250 mm or more can be used as a waterproof material for various waterproof products such as umbrellas and raincoats. A laminated fiber fabric having a water pressure resistance of 2000 mm or more can be used as a waterproof material for products requiring better waterproofness, such as raincoats and ski wear. When the laminated fiber fabric is used as a material for mountaineering equipment, rider rainwear, etc., the water pressure resistance of the laminated fiber fabric is preferably 100 kPa or more, when measured by JIS L1092 Water Resistance Test (Hydrostatic Pressure Method) Method B (high water pressure method).
[0118] 3. Manufacturing method of laminated fiber fabric The laminated fiber fabric described above can be manufactured, for example, by the following method. In one embodiment, the manufacturing method of the laminated fiber fabric includes treating a fiber fabric with a first treatment liquid to obtain a water-repellent fabric (S1), and treating one side of the water-repellent fabric with a second treatment liquid (S2). The first treatment liquid contains a non-fluorine-based water repellent agent. The second treatment liquid contains the coating agent of the present disclosure.
[0119] 3.1 S1 In S1, a fiber fabric is treated with a first treatment liquid to obtain a water-repellent fabric. Specifically, by treating the fiber fabric with the first treatment liquid, a water-repellent coating is formed on at least a part of the fiber fabric, thereby obtaining the water-repellent fabric.
[0120] The first treatment liquid contains a non-fluorine-based water repellent. Specific examples of the non-fluorine-based water repellent are as described above. The first treatment liquid may be a solution, an emulsion, or a dispersion. The solvent of the first treatment liquid may be at least one selected from water, ethyl alcohol, methyl alcohol, isopropyl alcohol, isobutyl alcohol, toluene, mineral spirits, and the like. The first treatment liquid may contain various additives such as a crosslinking agent, a catalyst, an antioxidant, an ultraviolet absorbing agent, an antistatic agent, a softener, an antibacterial agent, a deodorant, an anti-slip agent, inorganic particles, and organic particles. The first treatment liquid may also contain a surfactant for dissolving, emulsifying, and dispersing each component in the solvent. The amount of the surfactant is preferably as small as possible in order to suppress the second treatment liquid from penetrating (stripping through) into the fiber fabric in S2 described later.
[0121] The method for treating the fiber fabric with the first treatment liquid may be a known method such as a dip-nip method, a gravure transfer method, a spray method, etc. From the viewpoint of productivity and processing stability, it is preferable to treat the fiber fabric with the first treatment liquid by the dip-nip method.
[0122] In S1, after the fiber fabric is treated with the first treatment liquid, it may be further subjected to a heat treatment as desired. The heat treatment method may be appropriately selected according to the material of the fiber fabric and the type of components contained in the first treatment liquid. For example, the heat treatment may be performed at 135°C or higher and 210°C or lower for 10 seconds or longer and 10 minutes or shorter. In addition, in S1, drying may be performed before the heat treatment. In this case, the drying may be performed at 60°C or higher and 135°C or lower for 10 seconds or longer and 10 minutes or shorter. The drying temperature is preferably lower than the heat treatment temperature. By performing drying before the heat treatment, a more uniform water-repellent coating can be formed on the fiber.
[0123] 3.2 S2 In S2, one side of the water-repellent fabric obtained in S1 is treated with a second treatment liquid. Specifically, by treating one side of the water-repellent fabric with the second treatment liquid, a coating agent film is formed on the one side of the water-repellent fabric, and a laminated fiber fabric is obtained.
[0124] The second treatment liquid includes the coating agent of the present disclosure. The second treatment liquid may be a solution, an emulsion, or a dispersion. The solvent of the second treatment liquid may be, for example, water. The second treatment liquid may include various additives such as a crosslinking agent, a catalyst, an antioxidant, an ultraviolet absorber, an antistatic agent, a softener, an antibacterial agent, a deodorant, a flame retardant, an infrared absorber, other water repellents, antislip agents, inorganic particles, organic particles, and pigments. The first treatment liquid may also include various organic solvents such as ethyl alcohol, propyl alcohol, and butyl alcohol. The second treatment liquid may also include a surfactant for dissolving, emulsifying, and dispersing each component in the solvent.
[0125] It is preferable that the surfactant as the penetrating agent is not contained, and even if it is contained, it is preferable that the amount is small. By not containing a penetrating agent in the second treatment liquid, or by containing a small amount of the penetrating agent, the second treatment liquid can be prevented from penetrating (stripping through) into the fabric. This makes it possible to more appropriately form a coating agent film on one side of the water-repellent fabric. The content of the penetrating agent in the second treatment liquid is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, from the viewpoint of preventing the second treatment liquid from impregnating the fabric. As the material of the penetrating agent, in the case of using water as a solvent, at least one selected from alkyl naphthalene sulfonate, dialkyl sulfosuccinate, dialkyl sulfosuccinate, alkyl benzene sulfonate, alkyl allyl ether with HLB of 10 or more, and diethanolamine, etc., can be mentioned, and in particular, the sodium salts of these can be mentioned. These are sold under the names Pelex NBL (manufactured by Kao Corporation), Pelex OTP (manufactured by Kao Corporation), Scorin SW (manufactured by Shin-Nakamura Chemical Co., Ltd.), etc.
[0126] In S2, the coating agent can be used after adjusting its viscosity to a level suitable for the processing device used. That is, the viscosity of the coating agent may be adjusted and used as the second processing liquid. The viscosity of the second processing liquid is not particularly limited, but is preferably 5,000 mPa·s to 50,000 mPa·s, and more preferably 5,000 mPa·s to 40,000 mPa·s. If the viscosity is too low, it may cause bleed-through, and if the viscosity is too high, it may cause smearing. In the present disclosure, the viscosity (mPa·s) of the second processing liquid is a value measured by putting 200 ml of the second processing liquid into a glass bottle with an inner diameter of 50 mm and using a B-type viscometer (Tokimec Co., Ltd., BM-type viscometer, measurement temperature (25°C)).
[0127] From the viewpoint of obtaining good applicability of the coating agent to the fiber fabric, it is preferable to adjust the viscosity of the second treatment liquid to a specific range. The viscosity can be evaluated by the PVI value. The PVI value is a printing viscosity index, and in the present disclosure, the viscosity of the second treatment liquid is measured under the above-mentioned viscosity measurement conditions at rotation speeds of 60 rpm and 6 rpm, and is calculated according to the following formula. PVI value = measured value at 60 rpm ÷ measured value at 6 rpm
[0128] The PVI value of the second treatment liquid is preferably 0.10 or more and 0.50 or less, more preferably 0.15 or more and 0.30 or less. When the PVI value is 0.10 or more, a sufficient amount of coating can be applied without causing smearing during coating, and processing suitability is demonstrated. On the other hand, when the PVI value is more than 0.50, the amount of coating may be excessive or the texture may become hard. The viscosity and stickiness of the second treatment liquid may be adjusted by changing the type and amount of the thickener.
[0129] The method for obtaining the second treatment liquid is not particularly limited, and includes a method of blending the resin (A) and the polyvalent metal salt (B) with optional components such as a thickener, stirring and mixing, and adjusting the viscosity, pH, solid content, etc. The order and method of blending each component can be changed as appropriate. As a method for stirring and mixing, a conventionally known stirring device or emulsifying and dispersing device can be used. The conventionally known stirring device or emulsifying and dispersing device is not particularly limited, and includes stirring devices and emulsifying and dispersing machines such as a propeller, colloid mill, bead mill, milder, homogenizer, ultrasonic homogenizer, homomixer, homodisper, nanomizer, ultimizer, and starburst.
[0130] The dispersed particles in the second treatment liquid preferably have an average particle diameter d(50) of 0.5 μm or more and 30 μm or less, and a maximum particle diameter d(max) of 200 μm or less, and more preferably have an average particle diameter d(50) of 0.5 μm or more and 20 μm or less, and a maximum particle diameter d(max) of 100 μm or less. If the average particle diameter d(50) is too large, or if the maximum particle diameter d(max) is too large, the product stability of the coating agent may decrease. On the other hand, if the average particle diameter d(50) is too small, it may be industrially undesirable because it requires a lot of time and cost to reduce the particle diameter. The particle diameter is measured by a laser diffraction / scattering type particle size distribution measuring device, and the particle diameter (median particle diameter) at which the integrated volume is 50% is defined as the average particle diameter d(50), and the particle diameter (maximum particle diameter) at which the integrated volume is 100% is defined as the maximum particle diameter d(max).
[0131] The pH of the second treatment liquid is preferably adjusted to 6.0 or more and 10.0 or less, and more preferably 7.0 or more and 9.0 or less. If the pH is too low or too high, the viscosity of the second treatment liquid may decrease and the product stability may decrease, resulting in an excessive amount of the second treatment liquid being applied to the fiber fabric and causing strike-through.
[0132] Examples of a method for treating one side of the water-repellent fabric with the second treatment liquid include a coating method using a gravure coater, a knife coater, a knife over roll coater, a bar coater, a reverse coater, or a gravure coater, or a spray method using a spray nozzle, etc. It is particularly preferable to apply the second treatment liquid to one side of the water-repellent fabric by a coating method.
[0133] In S2, after treating one side of the water-repellent fabric with the second treatment liquid as described above, the solvent and volatile substances are removed from the second treatment liquid, and further, a heat treatment is performed as necessary, so that a coating agent film can be formed on one side of the water-repellent fabric. The method for removing the solvent, etc. is not particularly limited. For example, the solvent can be removed by applying the second treatment liquid to one side of the water-repellent fabric and then performing a heat treatment. The heat treatment may be performed, for example, at 135°C or higher and 240°C or lower for 10 seconds or longer and 10 minutes or shorter. Furthermore, drying may be performed before performing the heat treatment. The drying may be performed at 60°C or higher and 135°C or lower for 10 seconds or longer and 10 minutes or shorter.
[0134] The coating agent film formed by S2 may be porous or non-porous as described above. When the coating agent film contains a substance that is soluble in water (including acidic or alkaline water, hot water, warm water, etc.), the coating may be made into a porous film by soaping with alkaline water suited to each substance to remove the water-soluble substance contained in the coating agent film.
[0135] In S2, in order to prevent the water-repellent fabric from being impregnated with the second treatment liquid, one side of the water-repellent fabric may be subjected to a calendaring process before being treated with the second treatment liquid.
[0136] In S2, after forming a coating film on one side of the water-repellent fabric, at least one of water-repellent, deodorizing, ultraviolet shielding, infrared absorbing, antibacterial and deodorizing, antibacterial, and flame retardant finishes may be applied. In addition, a pattern, picture, design, etc. may be applied to the surface of the coating film using a pigment by a textile printing method or a gravure transfer method, or resin or fine particles may be applied to the coating film to change the texture or touch of the surface of the coating film or to impart anti-slip properties.
[0137] In addition, another fiber fabric such as a woven fabric or knitted fabric may be attached to the surface of the water-repellent fabric opposite to the coated surface using an adhesive or the like.
[0138] 4. Textile products The above-mentioned laminated fiber fabric is used as a material for various textile products. That is, the textile product includes the above-mentioned laminated fiber fabric in at least a part thereof. Specific examples of the textile products include, for example, coats, jackets, jumpers, down wear, hats, gloves, ski wear, windbreakers, work clothes, bags, tents, sleeping bags, down packs, etc. The textile products using the laminated fiber fabric of the present disclosure have excellent windproof properties, soft texture, excellent appearance quality, and excellent fashionability.
[0139] 5.Effects According to the coating agent, laminated fiber fabric, and manufacturing method thereof of the present disclosure, even for fiber fabrics processed with a non-fluorine-based water repellent, the coating agent film can be appropriately applied to one side of the fiber fabric without the coating agent striking through. Therefore, in addition to water repellency, a laminated fiber fabric having excellent windproofness (especially windproofness after washing) and padding loss prevention (downproofing), and excellent texture and appearance quality can be obtained. Even when a silicone-based water repellent is used as the non-fluorine-based water repellent, peeling of the coating agent film is suppressed, and a laminated fiber fabric having excellent flexibility can be obtained. According to such a laminated fiber fabric, various textile products such as clothes, shoes, bags, tents, etc. having excellent water repellency, windproofness, padding loss prevention (downproofing), and excellent texture and appearance quality can be provided. These textile products can also be expected to be waterproof. EXAMPLES
[0140] As described above, one embodiment of the technology of the present disclosure has been described, but the technology of the present disclosure can be modified in various ways other than the above embodiment without departing from the gist of the technology. The technology of the present disclosure will be described in more detail below while showing examples, but the technology of the present disclosure is not limited to the following examples.
[0141] 1. Synthesis of Resin (A) Resin (A) was synthesized using the following raw materials.
[0142] Radical polymerizable monomer (a1): ST: Styrene (glass transition temperature: 80°C) BzAc: benzyl acrylate (glass transition temperature: 6°C)
[0143] Radical polymerizable monomer (a2): MA: Methacrylic acid (glass transition temperature: 228°C) AA: Acrylic acid (glass transition temperature: 106°C)
[0144] Radical polymerizable monomer (a3): 2-EHA: 2-ethylhexyl acrylate (glass transition temperature: -70°C) BA: Butyl acrylate (glass transition temperature: -55°C) MMA: Methyl methacrylate (glass transition temperature: 105°C) HEMA: 2-hydroxyethyl methacrylate (glass transition temperature: -15°C)
[0145] Surfactants: Newcol (registered trademark) 707SF (polyoxyethylene polycyclic phenyl ether sulfate, 50% by weight solution, manufactured by Nippon Nyukazai Co., Ltd.) Newcol (registered trademark) 723 (polyoxyethylene polycyclic phenyl ether, manufactured by Nippon Nyukazai Co., Ltd.) TSP-20E (20 moles of ethylene oxide adduct of tristyrenated phenol) TSP-10ES (sulfuric acid ester salt of 10 moles of ethylene oxide adduct of tristyrenated phenol, 50% by weight solution)
[0146] 1.1 Synthesis Example 1 In a reaction apparatus, ion-exchanged water (327 parts by mass), Newcoal 707SF (5 parts by mass), Newcoal 723 (10 parts by mass), styrene (80 parts by mass) as monomer (a1), methacrylic acid (5 parts by mass) as monomer (a2), 2-ethylhexyl acrylate (275 parts by mass) as monomer (a3), and 2-hydroxyethyl methacrylate (40 parts by mass) as monomer (a3) were charged and stirred to prepare an emulsified mixture. After replacing the inside of the reaction apparatus with nitrogen gas, the inside temperature of the apparatus was heated to 80±5°C while stirring. In a separate container, ion-exchanged water (230 parts by mass), Newcoal 707SF (5 parts by mass), and a 10% by mass aqueous solution of ammonium persulfate (20 parts by mass) were charged to prepare an initiator solution. Next, the initiator solution was added dropwise to the above-mentioned emulsified mixture over a period of 3 hours. After the dropwise addition, the reaction was continued for another 3 hours while maintaining the internal temperature of the apparatus at 80±5°C. The internal temperature was then cooled to 25±5°C. Next, the mixture was neutralized with 25% ammonia water to adjust the pH to 7-9 and the resin concentration to 40% by mass, to obtain a resin emulsion (A-1). The aromatic ring ratio (calculated value) of the obtained resin was 15%, the acid value (calculated value) was 8 mgKOH / g, and the glass transition temperature (Tg, calculated value) was -30°C.
[0147] 1.2 Synthesis Examples 2 to 6 Resin emulsions (A-2), (A-3), (B-1), (B-2) and (B-3) were obtained by the same procedure as in Synthesis Example 1, except that the components were as shown in Table 1. The aromatic ring ratio (calculated value), acid value (calculated value) and glass transition temperature (Tg, calculated value) of each are shown in Table 1.
[0148] [Table 1]
[0149] 2. Preparation of laminated fiber fabric 2.1 Example 1 2.1.1 Preparation of textile fabric A knitted fabric made of polyester fiber (plain jersey, 46 gauge, 56 decitex / 96 filament, textured yarn, round cross section yarn) was dyed blue with a disperse dye and heat set.
[0150] 2.1.2 Water-repellent treatment The knitted fabric after dyeing and heat setting was treated with the following first treatment liquid by the dip-nip method, dried at 130°C for 1 minute, and then heat-treated at 170°C for 1 minute to obtain a water-repellent fabric. The water-repellent fabric had a water-repellent grade of 4. It was therefore confirmed that the fabric had excellent water repellency, and that a water-repellent coating containing a non-fluorinated water repellent agent was attached to the fiber surface of the fabric.
[0151] First treatment liquid: Non-fluorinated water repellent 5% Blocked isocyanate crosslinking agent 0.5% Stabilizer 1.0% water remainder
[0152] As the "non-fluorine-based water repellent", "a water repellent containing a silicone compound" was used in Example 1, Examples 2 to 17, 19 to 22, and Comparative Examples 1 to 4 described below, "a water repellent containing a silicone compound and a hydrocarbon compound" was used in Example 18, and "a water repellent containing a hydrocarbon compound" was used in Example 23. As the "blocked isocyanate-based crosslinking agent", NK Assist FU (manufactured by NICCA Chemical Co., Ltd.) was used. As the "stabilizing agent", Textport BG-290 (manufactured by NICCA Chemical Co., Ltd.) was used.
[0153] 2.1.3 Coating treatment The second treatment liquid described below was applied to one side of the water-repellent fabric by a coating method (the second treatment liquid was applied by floating using a knife coater). The fabric was then dried at 110°C for 60 seconds, and then heat-treated at 150°C for 30 seconds to obtain a laminated fiber fabric in which a coating agent film was laminated on one side of the water-repellent fabric.
[0154] Second treatment liquid: 100 parts of resin (A) shown in Table 2 Ammonia water (25%) 1 part Thickener 4 parts Calcium sulfate 1000ppm Isocyanate crosslinking agent 1 part
[0155] The thickener used was NEOSTEKER V-420 (manufactured by NICCA Chemical Co., Ltd.), and the isocyanate-based crosslinking agent used was NK ASSIST IS-100N (manufactured by NICCA Chemical Co., Ltd.).
[0156] 2.2 Examples 2 to 23 and Comparative Examples 1 to 4 A laminated fiber fabric was obtained in the same manner as in Example 1, except that the type of resin (A) and the type and amount of polyvalent metal salt (B) contained in the second treatment liquid were changed to those shown in Tables 2 or 3 below.
[0157] Comparative Example 1 is an example in which the aromatic ring ratio of the resin (A) exceeds 30%. Comparative Example 2 is an example in which the aromatic ring ratio of the resin (A) is below 0.5%. Comparative Example 3 is an example in which a monovalent metal salt is used as the salt (B) instead of a polyvalent metal salt. Comparative Example 4 is an example in which the salt (B) is not included.
[0158] 2.3 Reference Example 1, Comparative Examples 5 to 6 A laminated fiber fabric was obtained in the same manner as in Example 3, Comparative Example 1, or Comparative Example 2, except that in the first treatment liquid, a fluorine-based water repellent (NK Guard S-33, manufactured by Nicca Chemical Co., Ltd.) was applied instead of the silicone-based water repellent to obtain a water-repellent fabric.
[0159] 3. Evaluation of laminated fiber fabric 3.1 Water repellency The water repellency of the laminated fiber fabric was confirmed by conducting a test according to the JIS L1092:2009 Water Repellency Test Spray Method.
[0160] 3.2 Breathability The air permeability of the laminated fiber fabric was measured according to JIS L1096:2010 Method A (Fragile method). The lower the air permeability, the better the wind resistance.
[0161] 3.3 Durable air permeability After ten washings, the air permeability of the laminated fiber fabric was measured in the same manner as described above. It can be said that the lower the air permeability, the better the windproof property after washing.
[0162] 3.4 Film removability After ten washings as described below, the peelability of the coating film of the laminated fiber fabric was visually observed. Those with no change in the film were rated as pass (◯), and those with peeled or whitened films were rated as fail (×).
[0163] 3.4 Texture The laminated fiber fabric was checked by touching with hands and rated on a 5-point scale. A soft texture was rated as grade 5, and a hard texture was rated as grade 1. Among the experimental examples, comparative examples, and reference examples, the softest texture was rated as grade 5, and the hardest texture was rated as grade 1.
[0164] 3.5 Laundry Treatment The laminated fiber fabric was washed 10 times according to JIS L0217 103. Specifically, the fabric was washed 5 times with a washing time of 25 minutes and a rinsing time of 10 minutes, and this was repeated 10 times. After the 10 washings, the fabric was hung to dry once.
[0165] The following Tables 2 and 3 show the types and contents of the resin (A), neutralizer, thickener, and salt (B) contained in the second treatment liquid, the aromatic ring ratio, Tg, acid value, and PVI value of the resin (A), the mass ratio of the salt (B) to the mass of the unit (u2) of the resin (A), and the water repellency, air permeability, durable air permeability (air permeability after washing), film peelability, and texture of the laminated fiber fabric. In Tables 2 and 3, A-1, A-2, A-3, B-1, B-2, and B-3 correspond to those shown in Table 1, and all of them have a resin content of 40%. In Tables 2 and 3, the unit (u2) of the resin (A) means a unit derived from the radical polymerizable monomer (a2).
[0166] [Table 2]
[0167] [Table 3]
[0168] As is clear from the results shown in Tables 2 and 3 above, by using the coating agents (Examples 1 to 23, Reference Example 1) that satisfy the following (1) to (3), it is possible to appropriately form a coating film that has excellent windproof properties (especially windproof properties after washing) on a water-repellent fabric. (1) The coating agent contains a resin (A) and a polyvalent metal salt (B). (2) The resin (A) is one or both of a copolymer resin (A1) and a mixed resin (A2). (2-1) The copolymer resin (A1) has units (u1) derived from the radical polymerizable monomer (a1) represented by the above formula (1) and units (u2) derived from the radical polymerizable monomer (a2) represented by the above formula (2). (2-2) The mixed resin (A2) is a combination of a resin (A2-1) having the unit (u1) and a resin (A2-2) having the unit (u2). (3) The aromatic ring ratio of the resin (A) is 0.5% or more and 30% or less.
[0169] In contrast, when the aromatic ring ratio of resin (A) exceeded 30% (Comparative Examples 1 and 5), when the aromatic ring ratio of resin (A) was below 0.5% (Comparative Examples 2 and 6), when a monovalent metal salt was used instead of a polyvalent metal salt as salt (B) (Comparative Example 3), and when no salt (B) was included (Comparative Example 4), the durable air permeability was high, that is, the windproofness after washing was poor.
Claims
1. A coating agent comprising a resin (A) and a polyvalent metal salt (B), The resin (A) is one or both of a copolymer resin (A1) and a mixed resin (A2), The copolymer resin (A1) is A unit (u1) derived from a radical polymerizable monomer (a1) represented by the following formula (1), A unit (u2) derived from a radical polymerizable monomer (a2) represented by the following formula (2): having The mixed resin (A2) is A resin (A2-1) having the unit (u1), Resin (A2-2) having the unit (u2), It is a combination of The aromatic ring ratio of the resin (A) is 0.5% or more and 30% or less. Coating agent. 【Chemistry 1】 In formula (1), R 101 represents an optionally substituted C6-20 aryl group, R 102 represents hydrogen, an optionally substituted C1-24 saturated hydrocarbon group, or an optionally substituted C6-20 aryl group, X 101 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-, X 102 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-. 【Chemistry 2】 In formula (2), R 201 is a carboxy group, R 202 represents hydrogen or a C1-24 saturated hydrocarbon group which may have a substituent, R 203 represents hydrogen or a C1-24 saturated hydrocarbon group which may have a substituent, R 204 represents hydrogen, a carboxy group, or a C1-24 saturated hydrocarbon group which may have a substituent, X 201 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-, X 202 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-, X 203 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-, X 204 represents a single bond, a C1 to C10 divalent hydrocarbon group, -COO-, -O-, -CONH-, or -CO-.
2. the ratio of the mass of the polyvalent metal salt (B) to the mass of the unit (u2) constituting the resin (A) is 1.0% or more and 10.0% or less; The coating agent according to claim 1.
3. The glass transition temperature Tg of the resin (A) is −40° C. or higher and 0° C. or lower. The coating agent according to claim 1.
4. The acid value of the resin (A) is 1 or more and 20 or less. The coating agent according to claim 1.
5. A laminated fiber fabric having a fiber fabric, a water-repellent coating, and a coating agent coating, the water-repellent coating contains a non-fluorinated water-repellent agent, The water-repellent coating is formed on at least a portion of the fiber fabric, The coating agent film is formed on one side of the fiber fabric, the coating agent film is formed on at least a part of the surface of the water-repellent film, The coating agent film is made of the coating agent according to any one of claims 1 to 4. Laminated fiber fabric.
6. 1 cm 3 / cm 2 ・Has an air permeability of s or less, 2 cm 3 / cm 2 ・Has a durable air permeability of s or less, The laminated fiber fabric according to claim 5.
7. A method for producing a laminated fiber fabric, comprising: Treating a fiber fabric with a first treatment liquid to obtain a water-repellent fabric; and Treating one surface of the water-repellent fabric with a second treatment liquid; the first treatment liquid contains a non-fluorinated water repellent agent, The second treatment liquid contains the coating agent according to any one of claims 1 to 4. Manufacturing method.
8. applying the second treatment liquid to one side of the fiber fabric by a coating method; The method of claim 7.
9. The viscosity of the second treatment liquid is 5,000 mPa·s or more and 50,000 mPa·s or less. The method of claim 7.
Citation Information
Patent Citations
Processing method for adding windproof performance to cloth
JP2011127253A
Laminated fiber cloth and method for producing the same
JP2018009268A